SARS-CoV-2 infection elucidates features of pregnancy-specific immunity - Oh, Dong Sun; Kim, Eunha; Normand, Rachelly; Lu, Guangqing; Shook, Lydia L.; Lyall, Amanda; Jasset, Olyvia; Demidkin, Stepan; Gilbert, Emily; Kim, Joon; Akinwunmi, Babatunde; Tantivit, Jessica; et al. (Cell reports (Cambridge), 2024)
Pregnancy is a risk factor for increased severity of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and other respiratory infections, but the mechanisms underlying this risk are poorly understood. To gain insight into the role of pregnancy in modulating immune responses at baseline and upon SARS-CoV-2 infection, we collected peripheral blood mononuclear cells and plasma from 226 women, including 152 pregnant individuals and 74 non-pregnant women. We find that SARS-CoV-2 infection is associated with altered T cell responses in pregnant women, including a clonal expansion of CD4-expressing CD8+ T cells, diminished interferon responses, and profound suppression of monocyte function. We also identify shifts in cytokine and chemokine levels in the sera of pregnant individuals, including a robust increase of interleukin-27, known to drive T cell exhaustion. Our findings reveal nuanced pregnancy-associated immune responses, which may contribute to the increased susceptibility of pregnant individuals to viral respiratory infection. [Display omitted] •COVID-19 is associated with altered T cell responses in pregnant patients•Identified altered cytokine and chemokine levels in pregnant patients with COVID-19•scRNA-seq analyses reveal decreased ISG responses in pregnant patients with COVID-19•Severe/critical illness and maternal obesity are associated with additional immune dysfunction Oh et al. perform a comprehensive immune survey of COVID-19 in pregnant and non-pregnant women, identifying pregnancy-specific alterations in immune responses. These include altered T cell responses, monocyte function, chemokines and cytokines, and gut microbial composition. This work provides insights into how pregnancy shapes antiviral immunity.